Analisis Gaya Kepemimpinan Dalam Meningkatkan Efektivitas Kinerja Karyawan Di Bmt Al-Iktisab Kebun Baru - Rohmah, Siti (Ulumuna: Jurnal Studi Keilsman, 2025)
This research aims to determine leadership styles in increasing the effectiveness of employee performance at BMT Al-Iktisab Kebun Baru. This research uses qualitative research methods, with a descriptive approach and data collection techniques using observation and interviews with managers and employees as informants. The results obtained are [1] Employees must be able to collaborate effectively with their colleagues to achieve common goals and overcome challenges that may arise. [2] The democratic leadership style in increasing the effectiveness of employee performance at BMT Al-Iktisab shows good quality, namely by providing training for employees so that they can complete tasks well according to their own abilities and also in increasing the effectiveness of employee performance at BMT Al-Iktisab emulating the working principles of Rosulullah SAW, known as the STAF principles